2013
DOI: 10.4184/asj.2013.7.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Echinococcal Infection of the Lumbar Spine: An 11 Year Follow-up

Abstract: Spinal hydatid cyst is a rare occurrence in non endemic countries. We present a case of recurrent lumbar hydatid disease in a 21-year-old male who following initial treatment had a good functional outcome and healing for 8 years, following which he came back with complaints of low back ache and neurological deficit. Patient underwent a second surgery with global debridement of L3-L5 vertebrae followed by medical management for two years. He had a good surgical outcome with recovery from the neurological defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Albendazole and mebendazole are two most commonly used antihelminthic drugs. Studies have shown that prolonged albendazole treatment is a safe and effective alternative in late recurrences after bone hydatidosis surgery (1). In our case, we continued oral albendazol (400 mg daily) after the last surgery.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Albendazole and mebendazole are two most commonly used antihelminthic drugs. Studies have shown that prolonged albendazole treatment is a safe and effective alternative in late recurrences after bone hydatidosis surgery (1). In our case, we continued oral albendazol (400 mg daily) after the last surgery.…”
Section: Discussionmentioning
confidence: 73%
“…The former often chooses humans, sheep, and cattle as the intermediate host. A dog is the most common definitive host that transmits this larva to humans through direct contact (1). In endemic areas such as the Middle East, Central Asia, South America, East Africa, and Turkey, hydatidosis is relatively common, particularly in areas of poor hygiene (2).…”
Section: Introductionmentioning
confidence: 99%
“…This recurrence varies between 30% and 100% according to the series. [11][12][13][14][15][16] Medical treatment is still necessary before and after surgery in order to prevent recurrence, for which repeat surgery is often impossible and the results are disastrous. This treatment is based on albendazole at a dose of 400 mg per day for 6 to 18 months; 17 this treatment can be recommended as the only therapy in inoperable forms.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a very aggressive lesion because of the extension of the lesions and its constant recurrence. The literature recurrence ranges from 30% to 100% [ 10 ]. The diagnosis is difficult and based on the confrontation of clinical, biological, radiological and histological data.…”
Section: Discussionmentioning
confidence: 99%